PENERAPAN ILMU KRIMINALISTIK PADA PENYIDIKAN TINDAK PIDANA CABUL DENGAN KORBAN TUNA WICARA - Fajri, Agnes (UNES Law Review, 2020)
The application of criminalism in investigating obscene crimes against speech impaired victims by the PPA Unit of the Satreskrim Polres Agam is a science to help strategies in making light of cases. Criminal science is used to obtain information from victims as crown witnesses or victim witnesses, which is rather difficult to do. This is because the daily conditions of the victim cannot hear (deaf), do not speak (mute), so they cannot communicate properly like normal people, and never go to school. In this regard, investigators use criminalistic science with forensic psychology aids, forensic medicine aids and body language or sign science for the deaf. In forensic medicine, it is used by doing visum et repertum as evidence of violence against the reproductive organs. Forensic Psychology is used to examine the victim's psyche and his honesty about what he is going through. During the investigation into the investigation, the victim was also accompanied by a teacher from the Lubuk Basung Special Elementary School (SDLB). Victims are also examined using props or pictures to make it easier for victims to remember what happened to them, because the victim's memory as a person with a mute disability has limitations.